In Vivo Study of Fish Meal-Based RUFF (Ready-To-Use Fish Food) on Growth and Cognitive Development - Citta, Eleonora Pradnya Nirmala; Giriwono, Puspo Edi; Prangdimurti, Endang; Saraswati, Saraswati (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2025)
The prevalence of global malnutrition among children under 5 remains far from the SDG 30 target. As a countermeasure, RUTF (Ready to Use Therapeutic Food) was developed as an intervention and recovery measure. However, RUTF formulations use milk as the primary source of protein, which is scarce in some countries. That is why RUFF (Ready to Use Fish Food) is made, as a development of RUTF, using fish meal to create an even paste, improve formulations, and maximize the utilization of natural resources. This study aimed to create mackerel and pangas catfish RUFF and assess the impact of diet on growth and cognitive development in rodents. RUFFs were produced by preparing fish meals, which were then used to prepare RUFF formulations and were administered to rats for 28 days. Throughout the intervention, rats were counted for food consumption, weighed weekly, and subjected to the classic labyrinth. The pangas catfish and mackerel groups had the most significant weight gain. After 28 days, the rats were sacrificed to analyze brain development by weight and volume, as well as fatty acid profiles in blood plasma using GC-FID. The mackerel group had the largest brain weight and volume, at 1.747 g and 1.833 ml. The mackerel group also had the best cognitive performance and fastest average time in the labyrinth test. This supports that the mackerel group had the highest omega-3 content in both fish powder and blood plasma. The study concluded that experimental animals fed mackerel RUFF showed the best growth and cognitive development.